THE EFFECT OF PROMOTION, BRAND IMAGE AND CONSUMER PERCEPTION ON PURCHASE DECISIONS AT SHOPEE - Erick Ronaldo Hutapea; Triana Ananda Rustam (SEAN Institute, 2023)
The purchase decision in purchasing a product on the Shopee e-commerce that is currently happening is still high. However, behind the development of the Shopee application which still continues to exist, it does not mean that this online buying and selling site is not without a number of problems experienced by Shopee consumers which will have an impact on consumer decisions to make purchases on Shopee e-commerce. This study aims to determine the effect of promotion, brand image, and consumer perceptions on purchasing decisions at Shopee. The design of this study uses research design and quantitative research methods. Data collection techniques by distributing questionnaires to 384 respondents, namely Shoppe users with special characteristics that are in accordance with the objectives of this study. The results of this study indicate that promotion, brand image, and consumer perceptions partially and simultaneously have a significant effect on purchasing decisions. The results of the test for the coefficient of determination show that promotion, brand image, and consumer perceptions have a significant effect on purchasing decisions by 60.6 percent, while the rest are influenced by other variables not examined in this study.